Determinants of patient and physician global assessments of disease activity in anti-neutrophil cytoplasmic antibody-associated vasculitis - Rohde, Marius; Kernder, Anna; Acar, Hasan; Düsing, Christina; Fischer-Betz, Rebecca; Haase, Isabell; Mucke, Johanna; Sander, Oliver; Richter, Jutta; Filla, Tim; Schneider, Matthias; Chehab, Gamal (Frontiers in Medicine, 2023)
Objective To compare physician and patient assessments of global disease activity in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and to identify associated factors. Methods Global disease activity scores (0–10 points) were retrospectively analysed from physicians and patients with AAV at each outpatient visit from 2010 to 2020. We compared the scores and performed a linear regression with a random effects to identify associated factors. Results Patients (n=143, 1291 pairs, 52% female) had a mean 64 (± 15) years of age and a mean disease duration of 9 (± 7) years. Patients and physicians global disease activity assessments showed a moderate correlation (Pearson R 0.31, CI [0.23-0.52], p< 0.001). Linear regression showed a strong association between the physician-documented disease activity scores and serum CRP levels (β 0.22, CI [0.18, 0.28]), disease duration (β -0.022, CI [-0.04,-0.01]) and patients’ assessment of disease activity (β 0.08, CI [0.04, 0.12]). By contrast, patient assessments were strongly associated with the degree of pain (β 0.30, CI [0.25, 0.35]), functional limitations in daily living (HAQ, β 0.49, CI [0.21, 0.78]) and the global physical well-being (NRS, β 0.39, CI [0.32, 0.46]). Conclusion Patients’ and physicians’ assessments of disease activity correlated. High CRP levels and disease duration were associated with physician-assessed disease activity scores, while subjective limitations were associated with higher patient-assessed disease activity scores. These findings highlight and support the need to develop and evaluate patient-reported outcomes to assess disease activity in patients diagnosed with AAV.